Penerapan Disiplin Santri pada Mata Pelajaran Akidah Akhlak di MTs Al-Fathimiyah Karawang - Regita Ayu Dwietama; Tajuddin Nur; Yayat Herdiana (FONDATIA, 2022)
This study aims to determine the role of moral education in shaping the discipline of students at MTs Al-Fathimiyah Karawang. And the focus of this research study is to find out the implementation of Akhlak Akidah Education in Shaping Santri Discipline at MTs Al-Fathimiyah Karawang and moral education at MTs Al-Fathimiyah Karawang is implemented. In this study the authors used qualitative research. The research used is field research. Sources of data obtained from observations, interviews and documentation conducted at MTs Al-Fathimiyah Karawang. The results of the study indicate that the role of moral aqidah education greatly affects the discipline of students who are better, this is due to the existence of religious activities that are applied every day. Such as the reading of selected surahs, dhuha prayers and obligatory prayers in congregation. As well as the existence of guidance from Akhlak aqidah teachers who continue to provide direction, as well as in the learning process, namely in the delivery of teaching materials given to students. There are many factors that inhibit and support the role of moral aqidah education in shaping student discipline. However, if each supporting component can be fulfilled as a whole, it will facilitate the activities held at the cottage.